Digital Coding: Millimeter‐Wave Digital Coding Metasurfaces Based on Nematic Liquid Crystals (Adv. Theory Simul. 12/2019). Issue 12 (4th December 2019) - Wang, Qiang; Zhang, Xin Ge; Tian, Han Wei; Jiang, Wei Xiang; Bao, Di; Jiang, Hao Lin; Luo, Zhang Jie; Wu, Li Ting; Cui, Tie Jun
Abstract : In article number 1900141, Wei Xiang Jiang, Tie Jun Cui, and co‐workers propose and realize a type of millimeter‐wave (mmW) digital metasurface based on nematic liquid crystals (NLCs). By tuning the bias voltage loaded on the NLCs, different phase responses can be obtained from different metasurface elements and are represented by digital codes. These digital metasurfaces have promising applications for planar mmW devices and antennas.